Role of pepper MYB transcription factor CaDIM1 in regulation of the drought response - Lim, Junsub; Lim, Chae Woo; Lee, Sung Chul (Frontiers in Plant Science, 2022)
Abscisic acid (ABA) is a major phytohormone that plays important roles in stress responses, including regulation of gene expression and stomatal closure. Regulation of gene expression by transcription factors is a key cellular process for initiating defense responses to biotic and abiotic stresses. Here, using pepper (Capsicum annuum) leaves, we identified the MYB transcription factor CaDIM1 (Capsicum annuum Drought Induced MYB 1), which was highly induced by ABA and drought stress. CaDIM1 has an MYB domain in the N-terminal region and an acidic domain in the C-terminal region, which are responsible for recognition and transactivation of the target gene, respectively. Compared to control plants, CaDIM1-silenced pepper plants displayed ABA-insensitive and drought-sensitive phenotypes with reduced expression of stress-responsive genes. On the other hand, overexpression of CaDIM1 in Arabidopsis exhibited the opposite phenotypes of CaDIM1-silenced pepper plants, accompanied by enhanced ABA sensitivity and drought tolerance. Taken together, we demonstrate that CaDIM1 functions as a positive regulator of the drought-stress response via modulating ABA-mediated gene expression.